2017
DOI: 10.1037/hea0000546
|View full text |Cite
|
Sign up to set email alerts
|

Affective associations as predictors of health behavior in urban minority youth.

Abstract: The results are consistent with affective association research and support the development of health interventions for urban minority youth aimed at changing positive (rather than negative) affective associations. The consistency across behaviors and the lack of reliable interactive effects suggests that changing positive affective associations may benefit urban youth regardless of behavior domain, age, sex, negative affective associations, subjective norm, and cognitive beliefs. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…Regarding average family structure, 14% of this sample reported a single primary caregiver and 93% endorsed having siblings. The current sample is representative of high school students in this district in terms of race, ethnicity, and socioeconomic status, although the proportion of girls in this sample is higher than that of the school district (consistent with other health survey studies; e.g., Geers et al, 2017 ).…”
Section: Methodssupporting
confidence: 81%
“…Regarding average family structure, 14% of this sample reported a single primary caregiver and 93% endorsed having siblings. The current sample is representative of high school students in this district in terms of race, ethnicity, and socioeconomic status, although the proportion of girls in this sample is higher than that of the school district (consistent with other health survey studies; e.g., Geers et al, 2017 ).…”
Section: Methodssupporting
confidence: 81%
“…That is, as was found here, in many other domains affective and cognitive variables measured in the same context often do not correlate, 39,41 and positive and negative affect measures are often only weakly associated. 7,25 In the present context, the prospect that there are multiple and separable psychological processes after a treatment message suggests this variation should be given greater attention. One somewhat unexpected finding was that the treatment efficacy expectation scale and that pain experience expectation scale were only modestly correlated.…”
Section: Discussionmentioning
confidence: 84%
“…Although anxiety and diffuse positive and negative affect may operate similarly, it is also possible that each operates independently in placebo analgesia contexts. 7,25 For example, one possibility is that an analgesic treatment message raises positive affect but does not alter negative affect. To the best of our knowledge, no study has simultaneously assessed pretask anxiety, positive affect, and negative affect immediately after the delivery of a treatment message.…”
Section: Introductionmentioning
confidence: 99%
“…While the present study determined that income level moderates the relationship between affect and readiness to change, future studies should consider the influence of affect and attitudes as mediators of the demographic predictors of COVID-19 preventative behaviors. Future work should also aim to differentiate the impact of positive and negative affective responses, as differences can manifest in their predictive ability (Geers et al, 2017), and should also consider differences in self-conscious and hedonic affective states. For example, while not a primary focus of this study, both self-conscious and hedonic affective states were included in the measure of affect used here.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…The BAAM identifies cognitive variables (e.g., perceived norms) and affective variables (e.g., positive feelings) as independent predictors of intentions and health behaviors (e.g., Brown-Kramer and Kiviniemi, 2015). In line with such models, studies indicate that affective variables can be separate predictors of health actions and intentions from cognitive variables, such as attitudes (Lowe et al, 2002;Kiviniemi et al, 2007;Conner et al, 2013;Geers et al, 2017). For example, using simultaneous regression analyses, Lawton et al (2009) found that affective and instrumental attitudes were separate significant predictors of intentions to perform 11 different health behaviors, including alcohol consumption, flossing, and sunscreen use.…”
Section: Introductionmentioning
confidence: 95%